Prolificacy in Indian goat breeds is independent of FecB mutation - AHLAWAT, SONIKA; SHARMA, REKHA; MAITRA, A; RAJA, K N; VERMA, N K; TANTIA, M S (The Indian Journal of Animal Sciences, 2015)
Genetic studies on sheep prolificacy have indicated that litter size and ovulation rate is determined by the action of single genes, named fecundity (Fec) genes. In the present study, an attempt was made to screen Indian goats for the presence or absence of FecB mutation in BMPRIB gene which has been established as a prolificacy associated marker in sheep. Blood samples were collected and DNA was extracted from 200 goats with history of high twinning rate for three consecutive parities belonging to six prolific breeds (Black Bengal, Beetal, Barbari, Malabari, Sikkim and Jakhrana) of India. These goats were genotyped for the presence of FecB mutation by forced restriction fragment length polymorphism PCR technique. The efficiency and accuracy of the PCR-RFLP assay was confirmed by DNA sequencing of representative samples of each breed. All the goats were found to be homozygous non-carriers indicating absence of FecB mutation. Complete concordance was observed between the results obtained by PCRRFLP and direct DNA sequencing. These results suggest that fecundity of these prolific goat breeds is not linked to the same locus in BMPRIB gene as in some sheep breeds, and other polymorphism(s) or genes may be involved in governing the fecundity trait in caprines.